Use of MOOCs for Technology and Business Education - William Philip Wall; Bilal Khalid (Advances in educational technologies and instructional design book series, 2021)
Over the past decade, massive open online courses (MOOCs) as a new idea have been a highly debatable topic in online education. MOOCs were created to provide unlimited and free participation in higher education and made available to a wide range of recipients from all the corners of the world. Many developing countries rely on this alternative form of learning, which is totally different from the conventional classrooms, to increase access to education and improve the quality of higher learning. This has made educationalists in many developing countries express more interest in looking into how MOOCs can fit in and be implemented. This chapter explores the use of MOOCs in technology and business education.
Keywords: Online Learning and Analytics; Online and Blended Learning